Review: Sugarcane production: Impact of climate change and its mitigation - ASHOK K. SRIVASTAVA; MAHENDRA K. RAI (Biodiversitas Journal of Biological Diversity, 2012)
Srivastava AK, Rai MK. 2012. Review: Sugarcane production: impact of climate change and its mitigation 13: 214-227. Sugarcane is a climatic sensitive crop: therefore, its spatial distribution on the globe is restricted as per the suitability of various climatic parameters. The climate change, though, a very slow phenomenon is now accelerated due to natural, as well as enormous human activities disturbing the composition of atmosphere. The predications of various climatic models for probable rise in temperature, rainfall, sea level show an alarming condition in forthcoming decades. As the sugarcane is very sensitive to temperature, rainfall, solar radiations etc. therefore, a significant effect on its production and sugar yield is expected in future. It is also well known that sugarcane is one of the precious crops of the world and its end products i.e. sugar and ethanol have a continuous growing demand on global level. Hence, the studies related to good production of sugarcane in changing conditions of climate has become one among the front line area of research and is a major concern of scientist’s world over. Advance agronomic measures including development of suitable cane varieties susceptible to changed climatic conditions, land preparation, time and pattern of plantation, weed, disease and pest managements, nutrients managements, proper timing and adequate water management seems to be the affective measures for obtaining high production of crop with good quality juice in future.